2021
DOI: 10.1097/bpo.0000000000001850
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Postoperative Immobilization and Rehabilitation Following Reconstructive Hip Surgery in Nonambulatory Children With Cerebral Palsy

Abstract: Background: Despite being a common procedure, there are no standard protocols for postoperative immobilization and rehabilitation following reconstructive hip surgery in children with cerebral palsy (CP). The purpose of this study was to investigate variability in postoperative management and physical therapy (PT) recommendations among orthopaedic surgeons treating hip displacement in children with CP. Methods: An invitation to participate in an anonymous, online survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…While hip spica casts were classically considered the standard for immobilization following hip reconstructive surgery in children with CP, there is evidence that satisfactory outcomes can be obtained with alternative methods of postoperative immobilization ( 19 , 24 , 25 ). Spica casts have been actively avoided by families and care teams familiar with them because they are cumbersome and associated with other challenges during care ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While hip spica casts were classically considered the standard for immobilization following hip reconstructive surgery in children with CP, there is evidence that satisfactory outcomes can be obtained with alternative methods of postoperative immobilization ( 19 , 24 , 25 ). Spica casts have been actively avoided by families and care teams familiar with them because they are cumbersome and associated with other challenges during care ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of pelvic osteotomy techniques, when used, has also allowed many surgeons to view spica casting as optional. Miller et al recently showed that there is a tremendous lack of consensus in postoperative immobilization for CP hip reconstruction ( 19 ). This study sought to directly compare outcomes of hip reconstruction at a single institution in children that were immobilized with spica casts versus abduction pillows and better elucidate the complication rate of these methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another area of high variability is the varied postoperative immobilization techniques and protocols among surgeons. 25 The recovery from hip reconstruction and spine surgery is painful, with short-term improvements in Health Related Quality of Life (HRQoL) and caregiver burden. 26 After 5 years, the improvement in HRQoL and caregiver burden is maintained after hip reconstruction but declines to pre-surgical baseline after spine fusion.…”
Section: Figure 1 A) a 5-year-old With Bilateral Hip Subluxation (Rig...mentioning
confidence: 99%